Screen Position and Proprioception - Boucher, Marc (The International Journal of Screendance, 2014)
My contribution to critical and artistic dialogues within the intersecting fields of dance and screen-based images consists in examining the role of peripheral vision in the perception of dance in artistic contexts where projections are used. There is, as I will point out, sufficient evidence from phenomenological and neuro-physiological accounts to conclude that motion perception is affected by peripheral visual perceptions. Consequently, it is maintained that the spectator’s experience of dance, especially when screens are involved, depends to some degree on peripheral visual perception, which in turn contributes to proprioception.